Prototyping of catalyst pore-systems by a combined synthetic, analytical and computational approach: Application to mesoporous TiO2 - Novak, Vladimir; Ortel, Erik; Winter, Benjamin; Butz, Benjamin; Paul, Benjamin; Koci, Petr; Marek, Milos; Spiecker, Erdmann; Kraehnert, Ralph (Chemical Engineering Journal, 2014)
We propose a strategy that enables virtual prototyping and computational optimization of the pore system of a solid catalyst. The method combines template-assisted synthesis of porous metal oxides with tunable pore-space morphology, 3D imaging of the catalysts nanostructure by the state-of-the-art electron tomography in HAADF STEM mode, and multi-scale mathematical modeling that provides computational evaluation of the pore size distribution, effective diffusivity and tortuosity in the reconstructed system as well as macroscopic performance of the catalytic layer in terms of reactant conversion. This general approach is demonstrated on mesoporous TiO2 layers. (c) 2014 Elsevier B.V. All rights reserved.
Keywords: Catalyst; Nanocasting; Synthesis; Electron tomography; Multi-scale mathematical modeling; Diffusion